AUTHENTIC MATERIALS AS A TEACHING MEDIA TO MOTIVATE EFL STUDENTS - Fansury, Andi Hamzah (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The objective of the research was to know the use of an authentic material as teaching media to motivate students in learning English. The writer used qualitative design with the total number of samples in this research being 40 students. The researcher applied questionnaire and interview. The researcher analyzed the data using interactive model of analysis. In analyzing the numerical data, the writer used SPSS for windows. After conducted the research, the writer concludes that authentic materials can improve the students to understand the real context used by native speaker, improve students’ knowledge, Improve students’ English competence in both spoken and written, improve students’ vocabulary, introduce the culture of native speaker, improve students’ listening ability, motivate students to learn, motivate students to learn autonomously and it is compulsory subject from the school.